Letter (copy) : Asturian miners' orphans', etc. - Citrine, Walter, 1887-1983
030-0131-001 International WMC/WJB/AC/566 29th June, 1938. Mr. Ebby Edwards, Mineworkers' Federation of Great Britain, 50, Russell Square, W.C.1. Dear Mr. Edwards, ASTURIAN MINERS' ORPHANS',. etc. With reference to your letter of 28th June, in which you confirm the arrangement for the attendance here of your sub-committee on Tuesday next, 5th July, at 11 a.m., I am glad to be able to say that Mr. W. Schevenels will be able to be present. Mr. Elvin, unfortunately, will be in Brussels from Saturday until Tuesday inclusive, attending the fortieth Anniversary Congress of the Belgian C.G.T., so it will not be possible for him to meet your sub-committee on this occasion. Yours faithfully, General Secretary. 292/946/30/131